Shelf Design for Montessori Teaching Environment at Graha Ananda Kindergarten, West Bandung Regency - Nurul Fitriana Bahri; Gina Shobiro Takao; Martiyadi Nurhidayat (JURNAL RUPA, 2024)
The background of this study refers to the need for a learning environment that supports children's holistic development in accordance with Montessori principles. This research was motivated by the need to design optimal Montessori shelf in Graha Ananda Kindergarten, West Bandung Regency, as an important part of applying the Montessori approach in early childhood education. The urgency of this research is related to the critical role of Montessori shelf prototype in creating learning environments that support children's creativity and independence. The purpose of the study was to explore the visual aspects of Montessori shelf prototype, especially through the application of curve or wave variations on the side wooden structure. The research method used is qualitative with a case study approach, digging in-depth information related to the experiences and perceptions of Montessori shelf users at Graha Ananda Kindergarten. Data collection techniques include interviews and field surveys, while data analysis uses a descriptive approach to detail the visual elements and effectiveness of shelf design. The results of this study are expected to contribute to the improvement of Montessori shelf prototype, improve the quality of learning, and become a reference for similar educational institutions in applying Montessori principles in an early childhood environment. The results of this research indicate that the curved shelf design not only enhances aesthetics but also increases children's engagement and independence, aligning well with Montessori principles.